2006
DOI: 10.5213/inj.1630382.191
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Proportion of Hidden Patients Having Symptoms of Overactive Bladder and Why Has It Been Hidden in Female Outpatients Admitted to Hospital

Abstract: Purpose:To determine the proportion of patients with undetected symptoms of overactive bladder by using the overactive bladder-validated 8 (OAB-V8) screening questionnaire and investigate these symptoms were undetected in female patients who were hospitalized.Methods:We invited 2,250 female patients hospitalized in the Aegean region of Turkey to answer a self-administered questionnaire. The questionnaire included questions on evidence of lower urinary tract symptoms (OAB-V8), relevant medical history, and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Milsom et al (33) reported that 40% of individuals with OABS did not seek medical help. Üçer et al (34) showed that 57% of patients with OAB symptoms had not been previously admitted to hospital. In our study, this rate was found to be 13.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Milsom et al (33) reported that 40% of individuals with OABS did not seek medical help. Üçer et al (34) showed that 57% of patients with OAB symptoms had not been previously admitted to hospital. In our study, this rate was found to be 13.7%.…”
Section: Discussionmentioning
confidence: 99%